How Twylandia got her horn back - Wurfel, Marlene (My University, 2015)
Tales from the Lilypad's 1st birthday episode: a sequel to Twin Baby Unicorns. This original story, by Marlene Wurfel, is about how Twylandia the Unicorn, despite a jealous witches' curse that turned her into "just a horse," got her unicorn horn and the magical powers that come with it back.
Keywords: storytelling; children's stories